2021
DOI: 10.3389/fpls.2021.649888
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Is Associated With Heterosis of Salinity Tolerance in Brassica napus L.

Abstract: Heterosis is most frequently manifested as the superior performance of a hybrid than either of the parents, especially under stress conditions. Nitric oxide (NO) is a well-known gaseous signaling molecule that acts as a functional component during plant growth, development, and defense responses. In this study, the Brassica napus L. hybrid (F1, NJ4375 × MB1942) showed significant heterosis under salt stress, during both germination and post-germination periods. These phenotypes in the hybrid were in parallel w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 81 publications
(154 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, the shoot and root biomass of ecotype PTWG-PK was reduced ( p ≤ 0.001). Recently, a study by Zhang et al. (2021) has also confirmed that NO is associated with salinity tolerance in B. napus .…”
Section: Resultsmentioning
confidence: 83%
“…On the other hand, the shoot and root biomass of ecotype PTWG-PK was reduced ( p ≤ 0.001). Recently, a study by Zhang et al. (2021) has also confirmed that NO is associated with salinity tolerance in B. napus .…”
Section: Resultsmentioning
confidence: 83%
“…NO treatment has been shown to relieve seed aging and promote seed germination by increasing CS activity ( Mao et al., 2018 ). Moreover, NO treatment alleviates salt stress by increasing the CS and IDH activities in Brassica napus L. ( Zhang et al., 2021 ). α-KGDHC is not only the rate-limiting enzyme in the TCA cycle but also a target of ROS, and NO can increase its activity by S-nitrosylation ( Sun et al., 2007 ).…”
Section: Discussionmentioning
confidence: 99%